(untitled) (Clinics, 2020)
OBJECTIVES: This study aimed to verify the influence of Tai-Geiko on the physical and functional aspects of people with multiple sclerosis (MS). METHODS: This was a parallel-group, randomized trial with two arms. People with MS were allocated to an experimental group (EG) (n=10) and control group (CG) (n=09). The participants received multidisciplinary care supervised by a physiotherapist in the Tai-Geiko exercise. Participants underwent the assessments after the intervention. The Expanded Disability Status Scale (EDSS-maximum score of 6.0), strength test (kgf) using a dynamometer, Timed Up and Go mobility test (TUG), and stabilometric balance test (Platform EMG systems) were evaluated. Demographic data were recorded, including age, sex, comorbidities, lifestyle and classification of MS. Clinical Trials (ReBeC): RBR-4sty47. RESULTS: The EG group improved in 12 variables, and the CG improved in 3 variables. The following values were obtained for pre/postintervention, respectively: EG: lumbar force (38/52 kgf), TUG (11/9 s), locomotion velocity (519/393 ms); double task two (53/39 s); platform stabilometric trajectory: traversed get up (39/26 s) and sit (45/29 s); anteroposterior (AP) amplitude rise (11/8 cm) and sit (12.40/9.94 cm) and anteroposterior frequency rise (1.00/1.56 Hz) and sit (0.8/1.25 Hz) (po0.05); CG: right-hand grip force (26/29 kgf); TUG (9.8 /8.7 s) and AP (11.84 /9.53 cm) stabilometric amplitude at the sitting moment (po0.05), (3.2/5.99 Hz, p=0.01) and sit (3.47/5.01 Hz, p=0.04). CONCLUSION: Tai-Geiko practice can be suggested as complementary exercise in the rehabilitation of persons with MS.